A Stable Metal–Organic Framework Featuring a Local Buffer Environment for Carbon Dioxide Fixation. Issue 17 (15th March 2018) - He, Hongming; Sun, Qi; Gao, Wenyang; Perman, Jason A.; Sun, Fuxing; Zhu, Guangshan; Aguila, Briana; Forrest, Katherine; Space, Brian; Ma, Shengqian
Abstract: A majority of metal–organic frameworks (MOFs) fail to preserve their physical and chemical properties after exposure to acidic, neutral, or alkaline aqueous solutions, therefore limiting their practical applications in many areas. The strategy demonstrated herein is the design and synthesis of an organic ligand that behaves as a buffer to drastically boost the aqueous stability of a porous MOF (JUC‐1000), which maintains its structural integrity at low and high pH values. The local buffer environment resulting from the weak acid–base pairs of the custom‐designed organic ligand also greatly facilitates the performance of JUC‐1000 in the chemical fixation of carbon dioxide under ambient conditions, outperforming a series of benchmark catalysts. Abstract : A buffer strategy boosts the aqueous stability of a MOF over a broad range of pH values. The local buffer environment resulting from the weak acid–base pairs (green/blue bars on right of picture) of the custom‐designed organic ligand also greatly facilitates the performance of MOF in chemical fixation of carbon dioxide under ambient conditions.